2017
DOI: 10.1007/s10897-017-0189-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Telephone and Televideo Modes for Delivery of Genetic Counseling: a Randomized Trial

Abstract: Telephone and televideo have yielded equivalent patient satisfaction and psychosocial outcomes when compared to in-person genetic counseling, yet little is known about how they compare to one another. In this randomized controlled trial, veterans received genetic counseling via telephone or traveled to a clinic to participate via encrypted televideo. Knowledge and visit satisfaction were assessed 2 weeks later. Travel time, mileage, and out-of-pocket costs were calculated for videoconferencing. Qualitative int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 26 publications
2
51
2
Order By: Relevance
“…Further, some studies have suggested similar outcomes when comparing telephone consultations to in-person care (Buchanan et al, 2016;Chang et al, 2016;Fournier et al, 2018;Jacobs et al, 2016), and to video consultations (Voils et al, 2017). Some data also suggest that patients prefer, or are willing to utilize, telephone consultations more so than video consultations (Hardy & Grinzaid, 2017;Voils et al, 2017). However, providers continue to express concerns about whether telephone consultations can provide appropriate psychosocial care and education to patients (Bradbury et al, 2011;Burgess, Carmany, & Trepanier, 2016;Cohen et al, 2016), and the lack of physical exams and limitations on billing in telephone models are further barriers, as our data reflect.…”
Section: Program Technologymentioning
confidence: 97%
See 3 more Smart Citations
“…Further, some studies have suggested similar outcomes when comparing telephone consultations to in-person care (Buchanan et al, 2016;Chang et al, 2016;Fournier et al, 2018;Jacobs et al, 2016), and to video consultations (Voils et al, 2017). Some data also suggest that patients prefer, or are willing to utilize, telephone consultations more so than video consultations (Hardy & Grinzaid, 2017;Voils et al, 2017). However, providers continue to express concerns about whether telephone consultations can provide appropriate psychosocial care and education to patients (Bradbury et al, 2011;Burgess, Carmany, & Trepanier, 2016;Cohen et al, 2016), and the lack of physical exams and limitations on billing in telephone models are further barriers, as our data reflect.…”
Section: Program Technologymentioning
confidence: 97%
“…Some definitions place telephone consultations into another distinct (non-telegenetics) category (Cohen et al, 2013;Hilgart, Hayward, Coles, & Iredale, 2012). However, other works, including previous work of the RGNs, have included telephone consultations under the "telegenetics" umbrella (Voils, Venne, Weidenbacher, Sperber, & Datta, 2017). Although the NSGC Professional Status Survey separates telephone visits from webbased/video visits, it does not use the term "telegenetics" at all (National Society of Genetic Counselors, 2016).…”
Section: Backg Rou N Dmentioning
confidence: 99%
See 2 more Smart Citations
“…Genetic counselors have reported implementing alternative service delivery models to reduce wait times and to enhance access to care (Cohen, Huziak, Gustafson, & Grubs, ). Recently, randomized control studies have been conducted to compare a number of outcomes for various service delivery models (Biesecker et al, ; Buchanan et al, ; Voils, Venne, Weidenbacher, Sperber, & Datta, ). Educational components of genetic counseling are becoming automated with the implementation of videos, online educational tools, and decision aids that are used in some clinics to handle the increased demand for testing (Axilbund, Hamby, Thompson, Olsen, & Griffin, ; Birch et al, ).…”
Section: Historical Backgroundmentioning
confidence: 99%